PENGARUH KONFLIK KERJA, STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Di Universitas Yos Soedarso) - Muhammad Alif Rahman (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
This study aims to determine the effect of work conflicts, work stress and work environment on employee performance. The data used is primary data obtained from the distribution of questionnaires as much as 74 respondents to Yos Soedarso University. The analysis used is multiple linear regression. The results stated that the conflict work, stress work, and work environment, influence to the performance of employe.